Antithrombotic and Flow Drag‐Reducing Material for Blood‐Contacting Medical Devices. Issue 10 (23rd February 2023) - Tan, Justin Kok Soon; Chen, Elaine Shi An; Dong, Yibing; Fang, Hui; Koh, Cho Yeow; Kini, R. Manjunatha; Kim, Sangho; Leo, Hwa Liang; Yap, Choon Hwai
Abstract: Blood‐contacting medical devices are often associated with shear‐induced and contact activation thrombosis. Superhydrophobic materials have shown promise to reduce flow drag forces, but not contact activation. Here, a strategy of selectively grafting a potent anti‐thrombin compound on the tips of the surface microstructures of a superhydrophobic polytetrafluoroethylene foam, is presented, to concurrently achieve drag reduction and anti‐thrombosis. This work shows that two grafting approaches – Argon plasma or piranha solution treatment – followed by covalent cross‐linking can successfully graft the drug to the outer tips of the foam and provide anti‐thrombotic functionality. By avoiding grafting to the inner regions of the foam, the surface's drag reduction properties can be retained. The functional durability of the grafted surfaces is evaluated by strong water jetting, which demonstrates that the plasma approach can withstand substantial fluid shearing but not the piranha approach, although the plasma approach involves stronger compromise to the drag reduction capabilities. As the proposed selective grafting strategy is applied to a bulk foam, it can be complemented with a previously proposed strategy of supplying air pressure to the foam pores to bolster resistance to fluid impalement and plastron dissolution, allowing the material to be used in medical devices with high fluid pressures. Abstract : This work presents a strategy of selectively grafting anticoagulation compound to the outer regions of the surface microstructures of a superhydrophobic foam material, to concurrently achieve drag reduction (for blood damage reduction), and anti‐thrombosis, for use in blood‐contacting medical devices. This work demonstrates this with a biocompatible sintered polytetrafluoroethylene foam grafted with a potent anti‐thrombin drug, UV037.